2010
DOI: 10.2165/11313980-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Medication Costs of Patients with Cystic Fibrosis in Germany

Abstract: Costs of outpatient medication for CF patients significantly depend on age, co-morbidities and other clinical parameters. Hence, non-optimal treatment could lead to a significantly higher burden for the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
0
9
1
1
Order By: Relevance
“…However, the economic impact of CF has also increased over the past three decades. Many costs of illness studies have been conducted in Europe and the United States (U.S) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the economic impact of CF has also increased over the past three decades. Many costs of illness studies have been conducted in Europe and the United States (U.S) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Cost estimates for treatment based on data collected through regional CF centres, medical records, patient questionnaires, clinical trial and insurance claims or CF specific databases over the last three decades have demonstrated variable results. A wide range in costs, evaluated populations and different methodological approaches to calculate costs were also evident (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Where stated, medical drug treatment costs have contributed to anywhere between 12 to 85% of total costs.…”
Section: Introductionmentioning
confidence: 99%
“…The findings are significant from multiple perspectives. For instance, the associated annual pharmacological treatment costs associated with CF in adults (>17) is an estimated € 21,603 per patient/year (Eidt-Koch, Wagner, Mittenford & Graf von der Schulenburg, 2010). Our findings bolster the need to expand tobacco cessation programs available to CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a lot of these specialized care units are underfunded, and there are fewer economic incentives for hospitals to provide high-quality care for patients with rare diseases. Moreover, a study calculated mean annual outpatient costs for medication at 21,603 euro per patient [8]. These examples show why health care for people with rare diseases is costly, and that there are too few resources for treatment in some cases.…”
Section: Rare Diseases From An Economic Point Of Viewmentioning
confidence: 99%